Stable isotopes reveal opportunistic foraging in a spatiotemporally heterogeneous environment: Bird assemblages in mangrove forests. - Christina A Buelow; April E Reside; Ronald Baker; Marcus Sheaves (PLoS ONE, 2018)
Environmental heterogeneity can foster opportunistic foraging by mobile species, resulting in generalized resource and habitat use. Determining species' food web roles is important to fully understand how ecosystems function, and stable isotopes can provide insight into the foraging ecology of bird assemblages. We investigated flexibility of food choice in mangrove bird assemblages of northeast Australia by determining whether species' carbon and nitrogen isotopic values corresponded to foraging group classification described in the literature, such as groups of species that are omnivorous or insectivorous. Subsequently, we evaluated foraging group isotopic niche size, overlap, degree of individual specialisation, and the probable proportions of coastal resources that contribute to their collective diets. We found that mangrove birds are more opportunistic when foraging than expected from previous diet studies. Importantly, relationships between the dietary diversity of species within a foraging group and isotopic niche size are spatially inconsistent, making inferences regarding foraging strategies difficult. However, quantifying individual specialisation and determining the probable relative contributions of coastal resources to the collective diet of isotope-based foraging groups can help to differentiate between specialised and generalised foraging strategies. We suggest that flexibility in mangrove bird foraging strategy occurs in response to environmental heterogeneity. A complementary approach that combines isotopic analysis with other dietary information (collated from previous diet studies using visual observation or gut content analyses) has provided useful insight to how bird assemblages partition resources in spatiotemporally heterogeneous environments.